Perancangan Arsitektur Sistem Informasi Keluarga Berbasis Togaf ADM (Studi Kasus: Badan Kependudukan dan Keluarga Berencana Nasional) - Hasyim Adnan; Kemal Ade Sekarwati (Ridwan Institute, 2021)
National Population and Family Planning Board is a government-owned agency of the Republic of Indonesia which has the main task of carrying out government tasks in the field of population control and family planning. The design of information systems architecture is carried out using a framework by realizing harmony between information technology and the business processes that the organization runs. The framework used in this research is TOGAF using ADM. The final result of this research is an information system architecture as a guide in building SIGA BKKBN. If implemented, SIGA BKKBN will function as an information technology solution for the provision and management of BKKBN program data.